Work Life Balance to Overcome Stress in Hospitality Sector - H.M. , Moyeenudin; R. , Anandan (International Journal of Psychosocial Rehabilitation, 2020)
The predominance of employee stress is generally recognized in the hospitality sector through luxury hotels and restaurants, especially due to extended shifts and hostile social working hours, lack of job stability with continuous mismatched work requests, and working for additional hours without prior information. Continued shifts cause high work pressure. Generally, hotels and restaurants have unstable manpower due to work pressure. Likewise, hotel managers try to maintain their business with understaffed circumstances in order to have a high profit during busy hours, and this leads to feelings of anxiety. Left unchecked, delayed food service and the poor quality of food, the pressure has been seen as inconvenient to both the prosperity of hotel managers and associates. Thus, work-life balance (WLB) is a basic issue for hotel staff and intricate to have prosperity and fulfillment of needs because the workplace and nature of a hotel or restaurant lead to a lower level of WLB with organizational behavior. The objective of this study is to identify the work-life balance among the employees of the hotel and restaurant industry and, secondly, to overcome the factors that lead to stress in the hotel and restaurant sector.